News coverage on Islam and Muslims in Malaysia and Indonesia by Wall Street Journal and The Telegraph - Hassan, Fauziah (2017)
This study is essential to be carried out since many of the previous studies has been focusing too much of Muslims and Islamic religion in the West and the Middle-East countries. Therefore, this study is to investigate how two Western newspapers; specifically the Wall Street Journal (WSJ) and The Telegraph (TT) currently perceive Islam and Muslims, especially in Malaysia and Indonesia in three consecutive years: 2012 to 2014. This research aims to study the frequency of news reports, the types of the news sources, the themes and slants of the news. Two methodological approaches (quantitative and qualitative with ratio 40:60) have been applied to conduct this study. However, the priority was given to the qualitative approach; especially in the written report of the analysis. The quantitative content analysis has been used to determine the frequencies of news reporting and also to find out the types of news sources being quoted in the news reporting. The quantitative software known as SPSS Version 22 has been used with regard to analyse the statistical descriptive analysis. For qualitative, the researcher employed interpretative phenomenological analysis to determine the news themes, to find out the comparison of news themes and to characterize the direction of the news by using QSR NVivo 11. A total of 145 news articles were taken as samples for the analysis in which were selected through the constructive week sampling technique and specific keywords determined in this study. The findings of this research revealed that WSJ has been reporting about Islam and Muslims in Malaysia and Indonesia within the three years of study more frequently than did TT in which both newspapers were covered abundantly on Indonesian issues compared to Malaysian issues. Meanwhile, local sources especially the official sources such as policy makers, educational sources, uniformed officials and judicial institutions were frequently quoted compared to foreign news sources in the news reporting for both newspapers in two countries. Then, seven main themes were identified from the corpus of data: Religious Discourse, Islam and Violence, Governance and Administration, Law and Regulation, Politics, International Affairs and Peaceful Resolution. This study found that both newspapers focused on the theme of Religious Discourse for both Malaysian and Indonesian issues. Surprisingly, the findings revealed that the newspapers used in this study did not associate Islam and Muslims in Malaysia and Indonesia with the theme of Islam and Violence as only few news articles found under this them However, the Western media still do not favour Islam and Muslims around the world, including Islam and Muslims in Muslim-majority countries because the negative connotations in the news reporting still exist albeit not reporting issues related to violence.